THE SPIRITUAL ROLE OF PESANTREN IN SHAPING INDONESIAN CIVILIZED MUSLIMS - Jaenullah, Jaenullah; Sudadi, Sudadi (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2018)
As an Islamic educational Institution, Indonesian pesantren play roles in spiritually shaping Indonesian civilized Muslims. Since the beginning of pesantren spiritual teachings were installed pesantren founding fathers. Through such teachings, the students of pesantren can be the agents of Indonesian civilized Muslims who behave tolerantly, peacefully and friendly towards otherness and diversity in Indonesia. However, Pesantren have to develop in terms of their education system and management to deal with the phase of contemporary development of education. Yet, the core of spirituality in nuancing the pesantren education system and management has to be pertained and maintained. This article is to reveal such issues in relation to history and recent problems.